ANALYSIS OF PLANNING, GOVERNANCE AND INTEGRITY STRATEGIES THROUGH MEDIATION OF WORK HEALTH TOWARDS PROGRESS GOVERNING ORGANIZATIONS - Sitti Nurbaya (International Journal of Artificial Intelligence Research, 2022)
The objectives of the study analyzed planning, governance and integrity strategies directly and indirectly affecting the work and organizational performance of the South Sulawesi Provincial Government. This type of survey research approaches quantitative data sources from respondents and secondary from observation agencies. Data collection techniques use quisioner instruments. The study population of all employees was 11,067 and the random purposive sampling method was 5% as many as 386 respondents (Slovin formula). Data analysis using SEM analysis with the help of AMOS and SPSS computer programs. The results of the research directly and indirectly planning, governance and integrity strategies have a positive and significant effect on the health of work and organizational performance. Work health has a positive and significant effect on organizational performance. The better the planning strategy the easier it is to realize governance in the integration of work health into the performance of modern government organizations.